Doctor retention and distribution in post-apartheid South Africa: tracking medical graduates (2007-2011) from one university - Ann George; Duane Blaauw; Jarred Thompson; Lionel Green-Thompson (BMC, 2019)
Abstract Background Doctor emigration from low- and middle-income countries represents a financial loss and threatens the equitable delivery of healthcare. In response to government imperatives to produce more health professionals to meet the country's needs, South African medical schools increased their student intake and changed their selection criteria, but little is known about the impact of these changes. This paper reports on the retention and distribution of doctors who graduated from the University of the Witwatersrand, South Africa (SA), between 2007 and 2011. Methods Data on 988 graduates were accessed from university databases. A cross-sectional descriptive email survey was used to gather information about graduates' demographics, work histories, and current work settings. Frequency and proportion counts and multiple logistic regressions of predictors of working in a rural area were conducted. Open-ended data were analysed using content analysis. Results The survey response rate was 51.8%. Foreign nationals were excluded from the analysis because of restrictions on them working in SA. Of 497 South African respondents, 60% had completed their vocational training in underserved areas. At the time of the study, 89% (444) worked as doctors in SA, 6.8% (34) practised medicine outside the country, and 3.8% (19) no longer practised medicine. Eighty percent of the 444 doctors still in SA worked in the public sector. Only 33 respondents (6.6%) worked in rural areas, of which 20 (60.6%) were Black. Almost half (47.7%) of the 497 doctors still in SA were in specialist training appointments. Conclusions Most of the graduates were still in the country, with an overwhelmingly urban and public sector bias to their distribution. Most doctors in the public sector were still in specialist training at the time of the study and may move to the private sector or leave the country. Black graduates, who were preferentially selected in this graduate cohort, constituted the majority of the doctors practising in rural areas. The study confirms the importance of selecting students with rural backgrounds to provide doctors for underserved areas. The study provides a baseline for future tracking studies to inform the training of doctors for underserved areas.